Molecular Profiling of Mouse Models of Loss or Gain of Function of the KCNT1 (Slack) Potassium Channel and Antisense Oligonucleotide Treatment - Fangxu Sun; Huafeng Wang; Jing Wu; Imran H. Quraishi; Yalan Zhang; Maysam Pedram; Benbo Gao; Elizabeth A. Jonas; Viet Nguyen; Sijia Wu; Omar S. Mabrouk; Paymaan Jafar-nejad; et al. (Biomolecules)
The potassium sodium-activated channel subtype T member 1 (KCNT1) gene encodes the Slack channel KNa1.1, which is expressed in neurons throughout the brain. Gain-of-function variants in KCNT1 are associated with a spectrum of epilepsy syndromes, and mice carrying those variants exhibit a robust phenotype similar to that observed in patients. Kcnt1 knockout (KO) mice, however, have a normal lifespan without any epileptic phenotype. To understand the molecular differences between these two models, we conducted a comprehensive proteomic analysis of the cerebral cortices of Kcnt1 KO and Kcnt1R455H/+ mice, an animal model bearing a cytoplasmic C-terminal mutation homologous to a human R474H variant that results in EIMFS. The greatest change observed in Kcnt1 KO mice compared to the wild-type mice was the increased expression of multiple proteins of the inner mitochondrial membrane. Electron microscopy studies of cortical mitochondria from Kcnt1 KO mice further confirmed a significant increase in the density of mitochondrial cristae compared to that in wild-type mice. Kcnt1 reduction by a murine-specific Kcnt1 antisense oligonucleotide (ASO) in Kcnt1R455H/+ mice partially corrected the proteomic dysregulations in the disease model. The results support the hypothesis that ASO-mediated KCNT1 reduction could be therapeutically useful in the treatment of KCNT1 epilepsies.